The American Academy of Health Behavior 2022 Annual Scientifific Meeting: "The Science of Health Behaviors in Times of Crises" - Paul Branscum (New Prairie Press, 2022)
The American Academy of Health Behavior (AAHB) hosted its 22nd Annual Scientific Meeting at the Baker's Cay Resort in Key Largo, FL March 13-16, 2022. The meeting's theme was "The Science of Health Behaviors in Times of Crises". This publication describes the meeting theme and includes the refereed abstracts presented at the 2022 Annual Scientific Meeting.